Reinvention of public sector: Total quality management and change management - Karyotakis, Konstantinos M.; Moustakis, Vassilis S. (The European Journal of Applied Economics, 2014)
The present article provides a review of Total Quality Management (TQM) and Change Management in Public Sector. It highlights the special role of TQM in the Public Sector, the concept of Quality in Public Sector Services, the Innovation in Public Sector and the role that E-Government can play. Moreover, it emphasizes some Best Practices that have been applied in Greece and consists of innovative and interesting practices. It concludes by integrating all concepts discussed with the factors that shape change.